Manual therapy by general medical practitioners for nonspecific low back pain in primary care: the ManRück study protocol of a clinical trial - Schmiemann, Guido; Blase, Lena; Seeber, Christoph; Joos, Stefanie; Steinhäuser, Jost; Ernst, Stefanie; Großhennig, Anika; Hummers-Pradier, Eva; Lingner, Heidrun (Journal of chiropractic medicine, 2015)
BACKGROUND: Nonspecific low back pain (LBP) is a common reason for accessing primary care. Manual therapy (MT) may be an effective treatment, but data from clinical studies including relevant subgroups and clinical settings are sparse. The objective of this article is to describe the protocol of a study that will measure whether an MT protocol provided by general medical practitioners will lead to a faster pain reduction in patients with nonspecific LBP than does standard medical care. - METHODS/DESIGN: The study is an experimental pre-/postintervention design. The intervention consists of add-on MT treatment by general medical practitioners who have received MT training but are otherwise inexperienced in mobilization techniques. Participating general medical practitioners (n = 10) will consecutively recruit and treat patients before and after their training, serving as their own internal controls. The primary end point is a combined outcome assessing change in pain score over days 0 to 3 and time until pain is reduced by 2 points on an 11-point numeric pain scale and painkiller use is stopped. Secondary outcomes are patients' functional capacities assessed using a questionnaire, amount of sick leave taken, patient satisfaction, and referrals for further treatment. - TRIAL REGISTRATION: German clinical trials register: DRKS-ID DRKS00003240.
Gesehen am 06.07.2020